Axially-Symmetric Squeezed Films as Viscoelastic Flows with Dominating Extensions - Zahorski, S. (Engineering Transactions, 1986)
Axially-symmetric continuous squeezing flows of visco elastic fluids with simulated approach velocities of the discs are considered as thin-layer flows with dominating extensions [1]. Certain approximate solutions are presented and possible effects of the extensional viscosity function on the load-bearing forces are discussed in greater detail.